Evaluation of adult cases presenting with bleeding per rectum - R., Arun; Choksi, Dilip B.; Patil, Milind; Shah, Pooja; Chauhan, Sahdevsinh (International Surgery Journal, 2020)
Background: Aim of the study was to find out various proportion of diseases responsible for bleeding per rectum in adults and to find out diagnostic utility of anoproctoscopy, rigid sigmoidoscopy and colonoscopy for patients with bleeding per rectum. It also aims to find out the usefulness of other investigations like upper GI scopy, computed tomography etc., in undiagnosed cases. Methods: A total no of 129 patients with complaint of bleeding per rectum were included in the study. All cases were subjected to anoproctoscopy and rigid sigmoidoscopy. Colonoscopy was done in cases with severe or recurrent bleeding which were undiagnosed by sigmoidoscopy. If colonoscopy does not reveal the diagnosis upper GI scopy or computerized tomography (CT) angiography was done. Results: At the end of evaluation of 129 cases with bleeding per rectum, the cause for bleeding identified in 101 cases (78.3%). 28 cases (21.7%) remain undiagnosed. Conclusions: Large bowel endoscopy increases the diagnostic yield in patients with bleeding per rectum. Rigid sigmoidoscopy is a safe OPD based procedure, recommended in all patients presenting with bleeding per rectum and if the cause for bleeding per rectum cannot be diagnosed by rigid sigmoidoscopy, then colonoscopy is indicated. Even colonoscopy is not diagnostic, then the other investigations like upper GI scopy and CT angiography can be done to identify the source of bleeding.